2003
DOI: 10.4049/jimmunol.170.4.2083
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles of IL-4 in Lung Injury and Fibrosis

Abstract: Increased lung IL-4 expression in pulmonary fibrosis suggests a potential pathogenetic role for this cytokine. To dissect this role, bleomycin-induced pulmonary inflammation and fibrosis were analyzed and compared in wild type (IL-4+/+) vs IL-4-deficient (IL-4−/−) mice. Lethal pulmonary injury after bleomycin treatment was higher in IL-4−/− vs IL-4+/+ mice. By administration of anti-CD3 Abs, we demonstrated that this early response was linked to the marked T lymphocyte lung infiltration and to the overproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
189
0
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 207 publications
(212 citation statements)
references
References 57 publications
(55 reference statements)
11
189
0
8
Order By: Relevance
“…It is noteworthy that T helper cell type-2 cytokines are strongly implicated in tissue remodeling and fibrosis in other tissues. [39][40][41] In conclusion, our study demonstrates that eosinophil recruitment to the esophagus is associated with tissue remodeling. First, we show impressive collagen accumulation in the epithelial and subepithelial mucosa of esophageal biopsy specimens from human EE patients.…”
Section: Discussionsupporting
confidence: 54%
“…It is noteworthy that T helper cell type-2 cytokines are strongly implicated in tissue remodeling and fibrosis in other tissues. [39][40][41] In conclusion, our study demonstrates that eosinophil recruitment to the esophagus is associated with tissue remodeling. First, we show impressive collagen accumulation in the epithelial and subepithelial mucosa of esophageal biopsy specimens from human EE patients.…”
Section: Discussionsupporting
confidence: 54%
“…Recent studies have shown that several Th2 cytokines are expressed in RILF. Buttner et al (9) and Huaux et al (10) reported elevated levels of the type 2 cytokine interleukin (IL)-4 in rats during RILF. Tabata et al (11) showed that all-trans-retinoic acid prevents RILF by suppressing the expression of IL-6 in mice lung tissue after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse lung fibroblasts were isolated from lung tissue by mincing and enzymatic digestion, as previously described (33). Cells were cultured in complete medium composed of DMEM supplemented with 10% FBS and antibiotics (Invitrogen).…”
Section: Mouse Lung Fibroblast Culturementioning
confidence: 99%